The quarterly journal of economics. - Harvard University (Oxford : Oxford University Press, 1886)
The Quarterly Journal of Economics is the oldest professional journal of economics in the English language. Edited at Harvard University's Department of Economics, it covers all aspects of the field. QJE is invaluable to professional and academic economists and students around the world.
"Published on behalf of President and Fellows of Harvard University"--Home page.
Description based on online resource; title from home page (viewed on September 30, 2016).
Keywords: Economics -- Periodicals